Evaluasi Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah Negeri 6 Langkat - Annisa Yulia Nuri; Sapri Sapri; Ihdatul Wardah Chaniago; Ikhrawati Suriani; Rahma Rahma; Ade Syahputra; Satria Hutabarat; Nurmadayanti Nurmadayanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
A This research examines the evaluation of students with UAS/UTS on understanding Arabic. It is hoped that the evaluation results can become a benchmark for the success of the Arabic language learning process and become input for improving the quality of Arabic language learning. The method used in this research is literature and literature study which is also assisted by instrument information via Google. The aim of this research is to determine the development of Arabic language learning in Indonesia. The results of this research are that the author can say that the management of learning assessment at MIN 6 LANGKAT is running well in terms of planning, organization, implementation and supervision. In learning assessments at MIN 6 LANGKAT, all stakeholders from managers to lecturers are directly or indirectly involved in monitoring the implementation of assessments, academics, including assessments.